Effect of coffee consumption on liver enzymes (alanine transaminase, aspartate transaminase and alkaline phosphatase), total and conjugated bilirubin levels among students in Nnewi - Amah, Ubou K.; Analike, Adamma R.; Uzodinma, Somadina S.; Ogbodo, Chukwuemeka E.; Nnamdi, Chinonso J.; Njoku, Chidiadi M.; Agudi, Chibuike C.; Amah, Akuma K.; Obi-Ezeani, Chikaodili N. (International Journal of Research in Medical Sciences, 2020)
Background: Coffee has a number of bioactive compounds that have beneficial effects on human health in general and more importantly is the fact that coffee consumption has positive impact on the liver function. The present study investigated the effect of coffee consumption on liver enzymes: alanine transaminase (ALT), aspartate transaminase (AST) and alkaline phosphatase (ALP), total bilirubin (TB) and conjugated bilirubin (CB) levels among student in Nnewi. Methods: A total of twenty-five (25) apparently healthy participants aged between 18 and 30 years which were randomly recruited from College of Health Sciences’ students to serve as both test and control group. Each participant was advised to abstain from coffee and similar beverages for a period of three weeks prior to the commencement of the study. Subsequently, in addition to their normal diet, each of the subjects was given 2 gm of coffee dissolved in 150 ml of hot water in which 50 mg of non-dairy creamer was added before breakfast daily for 28 consecutive days. 6 ml each of baseline and test samples (after an overnight fast) were collected at day 0 and 29 respectively from each participant. Liver enzymes such as ALT, AST, and ALP activity as well as TB and CB levels was determined using standard laboratory methods. Results: This showed significant reductions in the mean serum AST and ALT activity, TB and unconjugated bilirubin (UB) levels with no significant alterations in the mean ALP activity and CB level in participants studied after short-term coffee consumption. Conclusions: This study revealed the hepatoprotective effect of coffee intake at short term basis.